The Higher Levels of Physical Activity Associated with Higher VO2max among Elderly - Dewa Ayu Putri Hartaningrum; Ida Ayu Astiti Suadnyana; I Putu Prisa Jaya (Physical Therapy Journal of Indonesia, 2022)
Background: The elderly are very sensitive to disease and health problems. The lack of economic support, such as nutritious food as the source of energy, is the most often cause of health problems in the elderly. Reduced energy in the elderly's body causes the elderly's lack of physical activity, which affects the VO2max level of the elderly. Objective: The purpose of this study was to determine the relationship between physical activity and VO2max in the elderly. Methods: The research design was a cross-sectional study conducted in March 2021 with a population of all elderly in Banjar Tegalnarungan, Sobangan Village, Mengwi District, Bali, Indonesia, who met the inclusion and exclusion criteria. The sampling technique in this study was total sampling and obtained 38 people. This study used the International Physical Activity Questionnaire questionnaire and 6 Minutes Walking Test to measure the physical activity levels and VO2max, respectively. Data were analyzed by computer software, namely Somers'd to determine the relationship between physical activity and VO2max in the elderly. Results: The results showed a significant relationship between physical activity and VO2max, resulting in p < 0.001. Conclusion: There is a significant positive relationship between physical activity and VO2max in the elderly, which represents the higher the physical activity level, the higher VO2max belongs to the elderly.